2002
DOI: 10.1289/ehp.02110575
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ambient coarse particulate matter on asthma hospitalization in children: case-crossover and time-series analyses.

Abstract: In this study, we used both case-crossover and time-series analyses to assess the associations between size-fractionated particulate matter and asthma hospitalization among children 6-12 years old living in Toronto between 1981 and 1993. Specifically, we used exposures averaged over periods varying from 1 to 7 days to assess the effects of particulate matter on asthma hospitalization. We calculated estimates of the relative risk of asthma hospitalization adjusted for daily weather conditions (maximum and minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
2
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(113 citation statements)
references
References 39 publications
5
102
2
4
Order By: Relevance
“…This caution means that we do not need to discount selectively our marginally significant (P ¼ 0.058) estimate of a protective effect of CO on COPD at the 1-day lag. Moreover, the lags that we found to be significant were longer than we expected a priori Atkinson et al, 2001), although associations at the 3-day lag have been reported (Norris et al, 2000;Lin et al, 2002). Particulate matter is a diverse mix of solid and liquid, organic and inorganic particles, some of which may be causing a health effect.…”
Section: Discussioncontrasting
confidence: 47%
“…This caution means that we do not need to discount selectively our marginally significant (P ¼ 0.058) estimate of a protective effect of CO on COPD at the 1-day lag. Moreover, the lags that we found to be significant were longer than we expected a priori Atkinson et al, 2001), although associations at the 3-day lag have been reported (Norris et al, 2000;Lin et al, 2002). Particulate matter is a diverse mix of solid and liquid, organic and inorganic particles, some of which may be causing a health effect.…”
Section: Discussioncontrasting
confidence: 47%
“…Conceição et al 16 showed that the difference between results obtained using linear and additive models of Poisson regression is nominal and another study found that the results obtained using time-series and case-crossover analysis are also largely similar 17 .…”
Section: Discussionmentioning
confidence: 98%
“…4,7,16 A recent study observed that the estimated effect of multiple-day exposures to air pollution could be stabilized on 5 to 6 days. 17 In this study, we calculated 1-to 7-day exposure averages ending on the admission date as the exposures in the case period.Control periods of 2 weeks before and after the admission date were used in the bidirectional scheme to minimize autocorrelation between case and control exposures and to control for seasonal and long-term effects. 17,18 To be matched with the case period, exposures in the control period were expressed as 1-to 7-day averages for each pollutant ending on the date 2 weeks before and after the admission date.…”
mentioning
confidence: 99%